Internalization Policy for the Practice of Pancasila in Society - Purwo Susongko; Rahul Bandari; Unggul Sugiharti (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2021)
This study aims to: (1) arrange the form of measurement instrument of internalization and practice of Pancasila that refers to MPR Decree No. 1 of 2003, (2) test the construct validity of instrument items of measurement of Pancasila internalization and practice based on Rasch modeling. Design development instruments using procedural models ADDIE (Analysis, Design, Development, Implementation, Evaluation). The validity test of the construct includes the content, substantive, structural and external aspects based on Rasch modeling.. The test consisted of 45 statements and respondents were asked to give an agreement on all statements. Scoring of test testees' responses can be done well with Rasch modeling. The instrument of internalization and practice of Pancasila has fulfilled the construct validity seen from the content, substantive, structural and external aspects. It conclude that the form of tests used can be widely applied and can be presented using information technology.